Management of acute mesenteric ischaemia: Results of a worldwide survey. (April 2023) - Hess, Benjamin; Cahenzli, Martin; Forbes, Alastair; Burgos, Rosa; Coccolini, Federico; Corcos, Olivier; Holst, Mette; Irtun, Øivind; Klek, Stanislaw; Pironi, Loris; Rasmussen, Henrik Højgaard; Serlie, Mireille J.; et al.
Summary: Background: Acute mesenteric ischaemia (AMI) is a condition with high mortality. This survey assesses current attitudes and practices to manage AMI worldwide. Methods: A questionnaire survey about the practices of diagnosing and managing AMI, endorsed by several specialist societies, was sent to different medical specialists and hospitals worldwide. Data from individual health care professionals and from medical teams were collected. Results: We collected 493 individual forms from 71 countries and 94 team forms from 34 countries. Almost half of respondents were surgeons, and most of the responding teams (70%) were led by surgeons. Most of the respondents indicated that diagnosis of AMI is often delayed but rarely missed. Emergency revascularisation is often considered for patients with AMI but rarely in cases of transmural ischaemia (intestinal infarction). Responses from team hospitals with a dedicated special unit (14 team forms) indicated more aggressive revascularisation. Abdominopelvic CT-scan with intravenous contrast was suggested as the most useful diagnostic test, indicated by approximately 90% of respondents. Medical history and risk factors were thought to be more important in diagnosis of AMI without transmural ischaemia, whereas for intestinal infarction, plasma lactate concentrations and surgical exploration were considered more useful. In elderly patients, a palliative approach is often chosen over extensive bowel resection. There was a large variability in anticoagulant treatment, as well as in timing of surgery to restore bowel continuity. Conclusions: Delayed diagnosis of AMI is common despite wide availability of an adequate imaging modality, i.e. CT-scan. Large variability in treatment approaches exists, indicating the need for updated guidelines. Increased awareness and knowledge of AMI may improve current practice until more robust evidence becomes available. Adherence to the existing guidelines may help in improving differences in treatment and outcomes.